A Fully Biodegradable and Ultra-Sensitive Crack-Based Strain Sensor for Biomechanical Signal Monitoring - Lee, Jae Hwan; Bae, Jae Young; Kim, Yoon Nam; Chae, Minseong; Lee, Woo Jin; Lee, Junsang; Kim, Im Deok; Hyun, Jung Keun; Lee, Kang Sik; Kang, Daeshik; Kang, Seung Kyun (Advanced Functional Materials, 2024)
A fully biodegradable, ultra-sensitive, and soft strain sensor is pivotal for temporary, real-time monitoring of microdeformations, crucial in disease diagnosis, surgical precision, and prognosis of muscular, and vascular conditions. Nevertheless, the strain sensitivity of previous biodegradable sensors, denoted by gauge factor (GF) up to ≈100, falls short of requirements for complex biomedical monitoring scenarios, specifically monitoring cardio-cerebrovascular diseases with microscale variations in vascular surface strain. Here, a fully biodegradable, ultra-sensitive crack-based flexible strain sensor is introduced achieving GF of 1355 at 1.5% strain through integration of molybdenum (Mo) film, molybdenum trioxide (MoO3) adhesion layer, and polycaprolactone (PCL) substrate. Analysis of crack morphology of biodegradable thin-film metals, including Mo, tungsten (W), and magnesium (Mg), reveals material-dependent sensitivity and repeatability of crack-based strain sensors. The effect of the adhesion layer and polymer substrate is also investigated. Overall morphological studies on the sensor present a comprehensive understanding of metal film cracking behavior and corresponding performance characterization, showing significant potential for highly sensitive sensors. A hybrid membrane composed of candelilla wax (Cw), beeswax (Bw), and polybutylene adipate-co-terephthalate (PBAT) is introduced to provide hydrophobic, yet flexible encapsulation. In vivo, short-term (≈3 days) monitoring of vascular pulsatility underscores the potential of the sensing tool for rapid, accurate, and temporal disease diagnosis and treatment.
Keywords: Adhesion layer; Biodegradable electronics; Crack-based strain sensor; Disease diagnosis; Gage factors; Signal monitoring; Strain sensors; Thin film cracking; Ultrasensitive; Vascular monitoring; biodegradable electronics; crack-based strain sensor; encapsulation; thin film cracking; vascular monitoring